Psychological Empowerment and Job Satisfaction on Organizational Commitment among SME Employees - Lim Lee Ling; Ong Choon Hee; Tan Owee Kowang; Theresa Ho Char Fe; Teo Poh Chuin; Zurina Patrick; Chi-Hua Wu (Human Resource Management Academic Research Society. (Htmars), 2023)
The purpose of this study is to examine the relationship between employees’ psychological empowerment and job satisfaction towards their organizational commitment in the SMEs in Johor, Malaysia. The independent variables of this study are psychological empowerment and job satisfaction while the dependent variables are continuance commitment and normative commitment which are the two elements under organizational commitment. The research design of this study is using a quantitative and cross-sectional approach. An online survey questionnaire was employed to collect data and yield 388 responses. The findings revealed that psychological empowerment and job satisfaction were significantly related to the continuance and normative commitment. This research can offer essential information for organizations in the SME sectors to increase understanding of the elements of organizational commitment and implement effective strategies to retain committed employees in the organization and reduced turnover rate effectively. It further assists organizations in improving employees’ organizational commitment by way of their psychological empowerment and job satisfaction level to achieve organizational success.